Efficacy of trimethoprim-sulphamethoxazole prophylaxis to decrease morbidity and mortality in HIV-1-infected patients with tuberculosis in Abidjan, Côte d'Ivoire: a randomised controlled trial. - Wiktor SZ; Sassan-Morokro M; Grant AD; Abouya L; Karon JM; Maurice C; Djomand G; Ackah A; Domoua K; Kadio A; Yapi A; Combe P; et al. (Lancet, 1999)
Background: There is a high incidence of opportunistic infection among HIV-1-infected patients with tuberculosis in Africa and, consequently, high mortality. We assessed the safety and efficacy of trimethoprim-sulphamethoxazole 800 mg/160 mg (co-trimoxazole) prophylaxis in prevention of such infections and in decrease of morbidity and mortality.Methods: Between October, 1995, and April, 1998, we enrolled 771 HIV-1 seropositive and HIV-1 and HIV-2 dually seroreactive patients who had sputum-smear-positive pulmonary tuberculosis (median age 32 years [range 18-64], median CD4-cell count 317 cells/microL) attending Abidjan's four largest outpatient tuberculosis treatment centres. Patients were randomly assigned one daily tablet of co-trimoxazole (n=386) or placebo (n=385) 1 month after the start of a standard 6-month tuberculosis regimen. We assessed adherence to study drug and tolerance monthly for 5 months and every 3 months thereafter, as well as rates of admission to hospital.Findings: Rates of laboratory and clinical adverse events were similar in the two groups. 51 patients in the co-trimoxazole group (13.8/100 person-years) and 86 in the placebo group (25.4/100 person-years) died (decrease In risk 46% [95% CI 23-62], p<0.001). 29 patients on co-trimoxazole (8.2/100 person-years) and 47 on placebo (15.0/100 person-years) were admitted to hospital at least once after randomisation (decrease 43% [10-64]), p=0.02). There were significantly fewer admissions for septicaemia and enteritis in the co-trimoxazole group than in the placebo group.Interpretation: In HIV-1-infected patients with tuberculosis, daily co-trimoxazole prophylaxis was well tolerated and significantly decreased mortality and hospital admission rates. Our findings may have important implications for improvement of clinical care for such patients in Africa.